Factors Affecting Low Students' Interest in Learning in Mathematics at Madrasah Ibtidaiyah - Mutmainnah Mutmainnah; Nur Khosiah; Tuhfatul Janan (Madrosatuna: Journal of Islamic Elementary School, 2022)
The current industrial era 4.0 is about to enter the industrial era 5.0, where education is increasingly advanced, the quality of education must be further improved so that it can compete with the outside world, which is increasingly technologically advanced. This study aims to determine the learning interest of class II MI students. Nurul Huda in mathematics on the banks of Probolinggo and what factors influence the low interest in learning for class II MI students. Nurul Huda in mathematics. The method used in this research is descriptive qualitative method. Data collection techniques using, observation, interviews, and documentation. The results of the research conducted at MI Nurul Huda on: 1) the interest in learning mathematics in class II MI Nurul Huda is classified as low, because there are still students who like to learn mathematics and repeat it at home, there are also students who do not like learning mathematics at home. house because there are lots of formulas and some don't like it because learning math is difficult. 2) The low interest in student learning in mathematics class II MI Nurul Huda, including: student psychological factors, unsupportive families, students' ability to interact.